2020
DOI: 10.1002/mgg3.1168
|View full text |Cite
|
Sign up to set email alerts
|

TP53 p.Arg337His geographic distribution correlates with adrenocortical tumor occurrence

Abstract: Background The p.Arg337His mutation of the TP53 is the most frequent germline missense variant associated with cancer described so far in this gene. It is mainly found in the South and Southeastern regions of Brazil, where it has been associated with a high incidence of pediatric adrenocortical (ACT) and choroid plexus tumors. The frequency and geographic distribution of this mutation is largely unknown, except for the Parana State, where a mean prevalence of 0.27% was reported. In the present study, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…A total of 29 cases of secondary malignancies/neoplasia were described [ 7 , 40 , 48 , 60 , 61 , 66 , 74 , 79 , 84 , 92 ], including the following entities: astrocytoma ( n = 4), osteosarcoma ( n = 3), liposarcoma ( n = 2), hepatoblastoma, chondrosarcoma, amelanotic melanoma, non-Hodgkin lymphoma, optic nerve glioma, kidney cell carcinoma, contralateral ACC, and choroid plexus papilloma ( n = 1 each), as well as lipoma ( n = 3) and hemangioma ( n = 2) as benign neoplasias. Even if there are only sporadic reports, nationwide analyses and genomic profiles [ 11 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ] hypothesize that the number of CPSs may be much higher than thought, and genetic counseling should be recommended to all parents and legal guardians of pediatric patients with ACC.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 cases of secondary malignancies/neoplasia were described [ 7 , 40 , 48 , 60 , 61 , 66 , 74 , 79 , 84 , 92 ], including the following entities: astrocytoma ( n = 4), osteosarcoma ( n = 3), liposarcoma ( n = 2), hepatoblastoma, chondrosarcoma, amelanotic melanoma, non-Hodgkin lymphoma, optic nerve glioma, kidney cell carcinoma, contralateral ACC, and choroid plexus papilloma ( n = 1 each), as well as lipoma ( n = 3) and hemangioma ( n = 2) as benign neoplasias. Even if there are only sporadic reports, nationwide analyses and genomic profiles [ 11 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ] hypothesize that the number of CPSs may be much higher than thought, and genetic counseling should be recommended to all parents and legal guardians of pediatric patients with ACC.…”
Section: Resultsmentioning
confidence: 99%
“…21 Another study assessed the frequency of the TP53 p.R337H variant by screening 32,130 newborns from São Paulo State, and it found that 68 (0.21%) were carriers. 22 These studies 21,22 have established that the germline TP53 p.R337H variant is widespread in South and Southeast Brazil and occurs at a population frequency of 0.3%. Although these original studies have not addressed the constitutive haplotype, screening haplotype-defining variants in newborns (n = 42,538) with an unknown history of cancer from South Brazil showed that 69% of p.R337H carriers also have the XAF1 p.E134* variant in the same haplotype.…”
Section: A Founder Tp53 Mutation Widespread In Brazilmentioning
confidence: 99%
“…In the largest population‐based screening study, 171,649 newborns from Paraná State were genotyped, and the p.R337H variant was identified in 461 patients (0.27%) 21 . Another study assessed the frequency of the TP53 p.R337H variant by screening 32,130 newborns from São Paulo State, and it found that 68 (0.21%) were carriers 22 . These studies 21,22 have established that the germline TP53 p.R337H variant is widespread in South and Southeast Brazil and occurs at a population frequency of 0.3%.…”
Section: A Founder Tp53 Mutation Widespread In Brazilmentioning
confidence: 99%
“…In more recent studies, prevalence of TP53 PV heterozygotes was proposed to reach 0.2% in Europeans [ 5 , 6 ]. In addition, a germline TP53 founder PV, c.1010G>A (p.Arg337His), widely referred as R337H, has been reported in Southern Brazil at a frequency of 1 in approximately 300 newborns [ 7 9 ], but tumor penetrance appears to be lower than that observed in carriers of DNA-binding domain (DBD) PV [ 10 13 ]. The arginine residue at codon 337 is involved in the protein oligomerization and functional data have shown that its replacement with histidine disrupts the tetramer form, making the domain unable to fully oligomerize in conditions of slightly elevated pH [ 14 ].…”
Section: Introductionmentioning
confidence: 99%